1997
DOI: 10.1038/42701
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of high mutation rates in experimental populations of E. coli

Abstract: Most mutations are likely to be deleterious, and so the spontaneous mutation rate is generally held at a very low value. Nonetheless, evolutionary theory predicts that high mutation rates can evolve under certain circumstances. Empirical observations have previously been limited to short-term studies of the fates of mutator strains deliberately introduced into laboratory populations of Escherichia coli, and to the effects of intense selective events on mutator frequencies in E. coli. Here we report the rise of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
706
2
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 831 publications
(742 citation statements)
references
References 28 publications
17
706
2
5
Order By: Relevance
“…Six populations evolved a mutator phenotype 4,19 , producing a sudden jump in total derived allele frequency (Fig. 2b).…”
Section: Reconstructing the Molecular Fossil Recordmentioning
confidence: 99%
“…Six populations evolved a mutator phenotype 4,19 , producing a sudden jump in total derived allele frequency (Fig. 2b).…”
Section: Reconstructing the Molecular Fossil Recordmentioning
confidence: 99%
“…A number of experimental and theoretical studies have shown that individuals with high mutation rates can have a selective advantage in changing environments [70][71][72]. Indeed, models predict that the random appearance of a mutator allele can accelerate the adaptive evolution of an entire population [73].…”
Section: Summary and Significancementioning
confidence: 99%
“…Simulations have shown how mutators could spread through asexual populations by hitch-hiking with beneficial mutations (Taddei et al, 1997;Tenaillon et al, 1999). They have also been demonstrated to increase the rate of adaptive evolution, at least in certain conditions (de Visser et al, 1999), though others have found that mutator lines did not differ in fitness (Sniegowski et al, 1997).…”
Section: Introductionmentioning
confidence: 99%